A Systematic Review and Meta-Analysis of Minimally Invasive Partial Nephrectomy Versus Focal Therapy for Small Renal Masses - Dong, Lin; Liang, Wang You; Ya, Lu; Yang, Liu; Qiang, Wei (Frontiers in Oncology, 2022)
Background Minimally invasive partial nephrectomy (MIPN) and focal therapy (FT) are popular trends for small renal masses (SRMs). However, there is currently no systematic comparison between MIPN and FT of SRMs. Therefore, we systematically study the perioperative, renal functional, and oncologic outcomes of MIPN and FT in SRMs. Methods We have searched the Embase, Cochrane Library, and PubMed for articles between MIPN (robot-assisted partial nephrectomy and laparoscopic partial nephrectomy) and FT {radiofrequency ablation (RFA), microwave ablation (MWA), cryoablation (CA), irreversible electroporation, non-thermal [irreversible electroporation (IRE)] ablation, and stereotactic body radiation therapy (SBRT)}. We calculated pooled mean difference (MD), odds ratios (ORs), and 95% confidence intervals (CIs) (CRD42021260787). Results A total of 26 articles (n = 4,420) were included in the study. Compared with MIPN, the operating time (OP) of FT had significantly lower (SMD, −1.20; CI, −1.77 to −0.63; I2 = 97.6%, P < 0.0001), estimated blood loss (EBL) of FT had significantly less (SMD, −1.20; CI, −1.77 to −0.63; I2 = 97.6%, P < 0.0001), length of stay (LOS) had shorter (SMD, −0.90; CI, −1.26 to −0.53; I2 = 92.2%, P < 0.0001), and estimated glomerular filtration rate (eGFR) of FT was significantly lower decrease (SMD, −0.90; CI, −1.26 to −0.53; I2 = 92.2%, P < 0.0001). However, FT possessed lower risk in minor complications (Clavien 1–2) (OR, 0.69; CI, 0.45 to 1.07; I2 = 47%, P = 0.023) and overall complications (OR, 0.71; CI, 0.51 to 0.99; I2 = 49.2%, P = 0.008). Finally, there are no obvious difference between FT and MIPN in local recurrence, distant metastasis, and major complications (P > 0.05). Conclusion FT has more advantages in protecting kidney function, reducing bleeding, shortening operating time, and shortening the length of stay. There is no difference in local recurrence, distant metastasis, and major complications. For the minimally invasive era, we need to weigh the advantages and disadvantages of all aspects to make comprehensive choices. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier PROSPERO (CRD42021260787).